Modeling Maturity Onset Diabetes of the Young in Pluripotent Stem Cells: Challenges and Achievements - Braverman-Gross, Carmel; Benvenisty, Nissim (Frontiers in Endocrinology, 2021)
Maturity onset diabetes of the young (MODY), is a group of monogenic diabetes disorders. Rodent models for MODY do not fully recapitulate the human phenotypes, calling for models generated in human cells. Human pluripotent stem cells (hPSCs), capable of differentiation towards pancreatic cells, possess a great opportunity to model MODY disorders in vitro. Here, we review the models for MODY diseases in hPSCs to date and the molecular lessons learnt from them. We also discuss the limitations and challenges that these types of models are still facing.